Efektivitas Tanggung Jawab Notaris dalam Objek Jual Beli yang Dipailitkan Berkaitan Akta Kuasa Menjual - Winarta, Kathleen Angel (UNES Law Review, 2023)
Implementation of the debtor's bankruptcy declaration decision for the law of loss of rights in the control and management of existing assets. All of the debtor's assets, which already exist and will be subject to general confiscation. The writing method is qualitative and analytical in nature and uses normative juridical research methods which focus on the source data, namely literature and library research. The research method concluded that bankruptcy would be completed if there was a re-submission of a lawsuit at the commercial court based on the object being transferred if another lawsuit was applied to the court referring to the bankrupt boedel. The results of the study are the responsibilities of a notary in a series of bankruptcies, namely compiling a deed in the transfer of assets, compiling a binding deed on material guarantees and compiling a notarial deed of private sales in a series of asset settlements. Basically, a notary is determined to have committed a criminal act if it can be proven that the legal action he carried out resulted in a loss for all creditors. What is new in this study has been noted in previous studies, but all research has its own characteristics. This research focuses on the effectiveness of notary responsibilities and the legal certainty of deed of power of attorney to sell objects which are bankrupt in the development of Indonesian law.